A phase 1/2 study of rigosertib in patients with myelodysplastic syndromes (MDS) and MDS progressed to acute myeloid leukemia. (January 2018) - Navada, Shyamala C.; Fruchtman, Steven M.; Odchimar-Reissig, Rosalie; Demakos, Erin P.; Petrone, Michael E.; Zbyszewski, Patrick S.; Holland, James F.; Silverman, Lewis R.
Highlights: Rigosertib stabilized bone marrow blasts and improved peripheral blood counts. Patients with response/stable disease had 1 yr longer survival than nonresponders. The recommended phase 2 dose of rigosertib was determined (1375 mg/m 2 /day). Hematologic toxicity was acceptable despite significant baseline cytopenias. Abstract: This Phase 1/2, dose-escalating study of rigosertib enrolled 22 patients with higher-risk myelodysplastic syndromes (MDS) (n = 9) and acute myeloid leukemia (AML; n = 13) who had relapsed or were refractory to standard therapy and for whom no second-line therapies were approved. Patients received 3- to 7-day continuous intravenous infusions of rigosertib, an inhibitor of Ras-effector pathways that interacts with the Ras-binding domains, common to several signaling proteins including Raf and PI3 kinase. Rigosertib was administered at doses of 650–1700 mg/m 2 /day in 14-day cycles. Initial dose escalation followed a Fibonacci scheme, followed by recommended phase 2 dose confirmation in an expanded cohort. Rigosertib was well tolerated for up to 23 cycles, with no treatment-related deaths and 18% of patients with related serious adverse events (AEs). Common AEs were fatigue, diarrhea, pyrexia, dyspnea, insomnia, and anemia. Rigosertib exhibited biologic activity, with reduction or stabilization of bone marrow blasts and improved peripheral blood counts in a subset of patients. Ten of 19 evaluable patients (53%) demonstrated bone marrow/peripheral blood responses (n = 4 MDS, n = 1 AML) or stable disease (n = 3 MDS, n = 2 AML). Median survival was 15.7 and 2.0 months for responders and non‐responders, respectively. Additional studies of rigosertib are ongoing in higher-risk MDS (NCT00854646).